Bifunctional catalyst, preparation method thereof and application of bifunctional catalyst in preparation of methanol by catalyzing carbon dioxide hydrogenation

By using a specific dual-function catalyst, the problem of low carbon dioxide conversion and methanol selectivity in the preparation of methanol by hydrogenation of carbon dioxide is solved, and efficient carbon dioxide adsorption and conversion is achieved, and the catalyst is highly stable and suitable for industrial applications.

CN119608173APending Publication Date: 2025-03-14INST OF COAL CHEM CHINESE ACAD OF SCI
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411907404.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

During the process of hydrogenation of carbon dioxide in the existing CuO-ZnO-Al2O3 catalysts, the carbon dioxide conversion rate and methanol selectivity are relatively low, and there is a 'seesaw' phenomenon.

Method used

A dual-function catalyst is adopted, including copper oxide, zinc oxide, aluminum oxide, yttrium oxide and magnesium oxide. The carbon dioxide adsorption capacity and conversion rate of the catalyst, methanol selectivity and yield are improved through the amount ratio and preparation method of the specific metal substance.

Benefits of technology

It has achieved efficient carbon dioxide adsorption and conversion, with a carbon dioxide conversion rate of 26.56%, a methanol selectivity of 76.46%, and a catalyst with high stability and long service life, making it suitable for industrial promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005204717740000131
    Figure BDA0005204717740000131
  • Figure BDA0005204717740000141
    Figure BDA0005204717740000141
  • Figure BDA0005204717740000142
    Figure BDA0005204717740000142
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysts, and particularly relates to a bifunctional catalyst, a preparation method thereof and application of the bifunctional catalyst in preparation of methanol by catalyzing carbon dioxide hydrogenation. According to the bifunctional catalyst provided by the invention, through specific metal amount, the overall performance of the catalyst is improved, the carbon dioxide adsorption capacity and conversion rate of the catalyst as well as the methanol selectivity and yield of the catalyst are improved, the carbon dioxide adsorption capacity is high, the carbon dioxide conversion rate reaches 26.56%, the methanol selectivity reaches 76.46%, and the stability is high. The invention also provides application of the bifunctional catalyst or the bifunctional catalyst prepared by the preparation method in catalysis of carbon dioxide hydrogenation for preparation of methanol. The bifunctional catalyst provided by the invention has the advantages of high carbon dioxide adsorption capacity and high activity in preparation of methanol by carbon dioxide hydrogenation, is suitable for catalyzing preparation of methanol by carbon dioxide hydrogenation, and is easy to separate since liquid-phase products only comprise methanol and water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a bifunctional catalyst and a preparation method thereof, and application thereof in catalyzing the hydrogenation of carbon dioxide to prepare methanol. Background Art

[0002] The production of methanol from carbon dioxide through thermal catalytic hydrogenation can not only produce important chemical raw materials, but also help reduce the stock of carbon dioxide. However, the above reaction usually requires the use of a catalyst, and the catalyst is required to have not only a strong carbon dioxide adsorption capacity, but also a high catalytic activity, which can be applied to different reaction scenarios and improve reaction efficiency.

[0003] At present, CuO-ZnO-Al catalysts are widely used in the production of methanol by hydrogenation of carbon dioxide. 2 O 3 The catalyst has good activity and methanol selectivity. 2 O 3 Catalysts usually have low carbon dioxide conversion rates and methanol selectivity, and there is a "seesaw" phenomenon between the two. Summary of the invention

[0004] The purpose of the present invention is to provide a bifunctional catalyst and a preparation method thereof and application in catalytic carbon dioxide hydrogenation to prepare methanol. The bifunctional catalyst provided by the present invention has high carbon dioxide adsorption capacity, conversion rate and methanol selectivity, with the carbon dioxide conversion rate reaching 26.56% and the methanol selectivity reaching 76.46%.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The invention provides a bifunctional catalyst, comprising metal oxides; the metal oxides comprise copper oxide, zinc oxide, aluminum oxide, yttrium oxide and magnesium oxide; the molar ratio of copper in the copper oxide to zinc in the zinc oxide is 50:25; the molar ratio of copper in the copper oxide to aluminum in the aluminum oxide is 50:15-25; the molar ratio of copper in the copper oxide to yttrium in the yttrium oxide is 50:1-10; the molar ratio of copper in the copper oxide to magnesium in the magnesium oxide is 50:27-150.

[0007] Preferably, the copper oxide is CuO.

[0008] Preferably, the zinc oxide is ZnO.

[0009] Preferably, the aluminum oxide is Al 2 O 3 .

[0010] Preferably, the yttrium oxide is Y 2 O 3 .

[0011] Preferably, the magnesium oxide is MgO.

[0012] Preferably, the particle size of the bifunctional catalyst is 250-425 μm.

[0013] The present invention also provides a method for preparing the bifunctional catalyst of the above scheme, comprising a coprecipitation method or a mechanical mixing method; the coprecipitation method comprises the following steps:

[0014] Mixing copper salt, zinc salt, aluminum salt, yttrium salt, magnesium salt and water to obtain a mixed salt solution, mixing sodium hydroxide and sodium carbonate to obtain a precipitant solution, dripping the mixed salt solution and the precipitant solution into water to obtain a mixed solution, maintaining the pH value of the mixed solution at 9.5-10.5 during the dripping process, aging the mixed solution and then calcining it to obtain the bifunctional catalyst;

[0015] The mechanical mixing method comprises the following steps: mixing copper salt, zinc salt, aluminum salt, yttrium salt and water to obtain a mixed salt solution, mixing sodium hydroxide and sodium carbonate to obtain a precipitant solution, dripping the mixed salt solution and the precipitant solution into water to obtain a mixed solution, maintaining the pH value of the mixed solution at 9.5-10.5 during the dripping process, aging the mixed solution and then calcining it to obtain an intermediate catalyst; and mixing the intermediate catalyst and magnesium oxide and grinding them to obtain the bifunctional catalyst.

[0016] The present invention also provides the use of the bifunctional catalyst described in the above scheme or the bifunctional catalyst obtained by the preparation method described in the above scheme in catalyzing the hydrogenation of carbon dioxide to prepare methanol.

[0017] The present invention provides a bifunctional catalyst. The bifunctional catalyst provided by the present invention improves the overall performance of the catalyst through a specific amount of metal, improves the catalyst's carbon dioxide adsorption capacity and conversion rate, methanol selectivity and yield, has a high carbon dioxide adsorption capacity, a carbon dioxide conversion rate of 26.56%, and a methanol selectivity of 76.46%. In addition, the bifunctional catalyst provided by the present invention has high stability, and at P = 5.0MPa, T = 270°C, GHSV = 6000mL mL cat -1 h -1 Under the condition of raw gas hydrogen / carbon dioxide (molar ratio) = 3, the conversion rate was maintained at about 26%, the selectivity was maintained at about 75%, and the yield was maintained at 0.58g gcat -1 h -1 It has a long service life of more than 720 hours, which is conducive to industrial promotion.

[0018] The present invention also provides a method for preparing the bifunctional catalyst described in the above scheme. The present invention adopts a coprecipitation method or a mechanical mixing method, which has simple steps, convenient operation, and is easy to realize industrial scale.

[0019] The present invention also provides the use of the bifunctional catalyst described in the above scheme or the bifunctional catalyst obtained by the preparation method described in the above scheme in catalyzing the hydrogenation of carbon dioxide to produce methanol. The bifunctional catalyst provided by the present invention has a high carbon dioxide adsorption capacity and a high activity for preparing methanol by hydrogenation of carbon dioxide, and is suitable for catalyzing the hydrogenation of carbon dioxide to produce methanol. The liquid phase products are only methanol and water, which are easy to separate. DETAILED DESCRIPTION

[0020] The invention provides a bifunctional catalyst, comprising metal oxides; the metal oxides comprise copper oxide, zinc oxide, aluminum oxide, yttrium oxide and magnesium oxide; the molar ratio of copper in the copper oxide to zinc in the zinc oxide is 50:25; the molar ratio of copper in the copper oxide to aluminum in the aluminum oxide is 50:15-25; the molar ratio of copper in the copper oxide to yttrium in the yttrium oxide is 50:1-10; the molar ratio of copper in the copper oxide to magnesium in the magnesium oxide is 50:27-150.

[0021] The bifunctional catalyst provided by the present invention comprises copper oxide; the copper oxide is preferably CuO.

[0022] The bifunctional catalyst provided by the present invention comprises zinc oxide; the zinc oxide is preferably ZnO.

[0023] The bifunctional catalyst provided by the present invention comprises aluminum oxide; the aluminum oxide is preferably Al 2 O 3 .

[0024] In the present invention, the molar ratio of copper in the copper oxide to aluminum in the aluminum oxide is preferably 50:15-25, specifically 50:15, 50:17, 50:18, 50:20, 50:21, 50:22, 50:24 or 50:25.

[0025] The bifunctional catalyst provided by the present invention comprises yttrium oxide; the yttrium oxide is preferably Y 2 O 3 .

[0026] In the present invention, the molar ratio of yttrium in the yttrium oxide to zinc in the zinc oxide is preferably 1 to 10:25, specifically 1:25, 3:25, 5:25, 6:25, 7:25, 9:25 or 10:25.

[0027] In the present invention, the molar ratio of copper in the copper oxide to yttrium in the yttrium oxide is preferably 50:1-10, specifically 50:1, 50:2, 50:3, 50:4, 50:5, 50:6, 50:7, 50:8, 50:9 or 50:10.

[0028] The bifunctional catalyst provided by the present invention comprises magnesium oxide; the magnesium oxide is preferably MgO.

[0029] In the present invention, the molar ratio of copper in the copper oxide to magnesium in the magnesium oxide is preferably 50:27-150, and specifically can be 50:27, 50:29, 50:30, 50:40, 50:50, 50:70, 50:90, 50:120 or 50:150.

[0030] In the present invention, the particle size of the bifunctional catalyst is preferably 250-425 μm, specifically 250 μm, 270 μm, 290 μm, 310 μm, 330 μm, 350 μm, 370 μm, 390 μm or 425 μm.

[0031] The present invention also provides a method for preparing the bifunctional catalyst of the above scheme, comprising a coprecipitation method or a mechanical mixing method; the coprecipitation method comprises the following steps:

[0032] Mixing copper salt, zinc salt, aluminum salt, yttrium salt, magnesium salt and water to obtain a mixed salt solution, mixing sodium hydroxide and sodium carbonate to obtain a precipitant solution, dripping the mixed salt solution and the precipitant solution into water to obtain a mixed solution, maintaining the pH value of the mixed solution at 9.5-10.5 during the dripping process, aging the mixed solution and then calcining it to obtain the bifunctional catalyst;

[0033] The mechanical mixing method comprises the following steps: mixing copper salt, zinc salt, aluminum salt, yttrium salt and water to obtain a mixed salt solution, mixing sodium hydroxide and sodium carbonate to obtain a precipitant solution, dripping the mixed salt solution and the precipitant solution into water to obtain a mixed solution, maintaining the pH value of the mixed solution at 9.5-10.5 during the dripping process, aging the mixed solution and then calcining it to obtain an intermediate catalyst; and mixing the intermediate catalyst and magnesium oxide and grinding them to obtain the bifunctional catalyst.

[0034] On the one hand, the present invention provides a coprecipitation method for preparing a bifunctional catalyst: the present invention mixes a copper salt, a zinc salt, an aluminum salt, a yttrium salt, a magnesium salt and water (referred to as the first water) to obtain a mixed salt solution. In the present invention, the copper salt, the zinc salt, the aluminum salt, the yttrium salt and the magnesium salt are preferably added according to the chemical composition of the bifunctional catalyst; the total concentration of the metal salt in the mixed salt solution is preferably 0.5 to 1 mol / L, specifically 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L or 1 mol / L.

[0035] In the present invention, the copper salt is preferably a soluble copper salt; the soluble copper salt is preferably one or more of copper nitrate and hydrated copper nitrate.

[0036] In the present invention, the zinc salt is preferably a soluble zinc salt; the soluble zinc salt is preferably one or more of zinc nitrate and hydrated zinc nitrate.

[0037] In the present invention, the aluminum salt is preferably a soluble aluminum salt; the soluble aluminum salt is preferably one or more of aluminum nitrate and hydrated aluminum nitrate.

[0038] In the present invention, the yttrium salt is preferably a soluble yttrium salt; the soluble yttrium salt is preferably one or more of yttrium nitrate and hydrated yttrium nitrate.

[0039] In the present invention, the magnesium salt is preferably a soluble magnesium salt; the soluble magnesium salt is preferably one or more of magnesium nitrate and hydrated magnesium nitrate.

[0040] In the present invention, the first water is preferably deionized water.

[0041] The present invention mixes sodium hydroxide and sodium carbonate to obtain a precipitant solution. In the present invention, the molar ratio of the sodium hydroxide and the sodium carbonate is preferably 3 to 6:1, specifically 3:1, 4:1, 5:1 or 6:1.

[0042] In the present invention, the total concentration of sodium hydroxide and sodium carbonate in the precipitant solution is preferably 1.5-2 mol / L, specifically 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L or 2 mol / L.

[0043] In the present invention, the mixed salt solution and the precipitant solution are dripped into water (referred to as the second water) to obtain a mixed solution. In the present invention, the dripping speed is preferably based on maintaining the pH value of the mixed solution at 9.5 to 10.5 during the dripping process, preferably 10.

[0044] In the present invention, the dropping temperature is preferably room temperature.

[0045] In the present invention, the dropwise addition is preferably performed under stirring conditions.

[0046] In the present invention, the second water is preferably deionized water.

[0047] In the present invention, the ratio of the total volume of the mixed salt solution and the precipitant solution to the volume of the second water is preferably 0.8-1.5:1, specifically 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1 or 1.5:1.

[0048] In the present invention, the volume ratio of the mixed salt solution to the precipitant solution is preferably 1:1-1.5, specifically 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4 or 1:1.5.

[0049] The present invention ages the mixed solution and then calcines it to obtain the bifunctional catalyst. In the present invention, the aging temperature is preferably 60-80°C, specifically 60°C, 65°C, 70°C, 75°C or 80°C, and the heat preservation aging time is preferably 10-15h, specifically 10h, 11h, 12h, 13h, 14h or 15h; the aging is preferably carried out under stirring conditions.

[0050] In the present invention, the aging preferably further comprises subjecting the obtained product to a first post-treatment; the first post-treatment preferably comprises: sequentially subjecting the aged product to cooling, solid-liquid separation, washing and drying.

[0051] In the present invention, the final temperature of the cooling is preferably room temperature; the solid-liquid separation is preferably filtration; the washing is preferably water washing; the water used for the washing is preferably deionized water; and the washing is preferably stopped when the washing liquid is neutral.

[0052] In the present invention, the drying temperature is preferably 80-100° C., specifically 90° C., and the heat preservation and drying time is preferably 10-15 h, specifically 12 h or 14 h.

[0053] In the present invention, the calcination temperature is preferably 300-700°C, specifically 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, or 700°C, and the heat preservation calcination time is preferably 4-6h, specifically 5h.

[0054] In the present invention, after the calcination, the obtained product is preferably subjected to a second post-treatment; the second post-treatment is preferably: cooling, tableting, crushing and screening the calcined product in sequence.

[0055] In the present invention, the final temperature of the cooling is preferably room temperature; the tableting pressure is preferably 5-15 MPa, specifically 10 MPa, and the holding time is preferably 10-30 min, specifically 20 min.

[0056] On the other hand, the present invention also provides a mechanical mixing method for preparing a bifunctional catalyst: the present invention mixes copper salt, zinc salt, aluminum salt, yttrium salt and water to obtain a mixed salt solution, mixes sodium hydroxide and sodium carbonate to obtain a precipitant solution, and drips the mixed salt solution and the precipitant solution into water to obtain a mixed solution, the pH value of the mixed solution is maintained at 9.5-10.5 during the dripping process, and the mixed solution is aged and then roasted to obtain an intermediate catalyst.

[0057] In the present invention, the preparation method of the intermediate catalyst is preferably the same as the preparation method of the bifunctional catalyst prepared by coprecipitation, the only difference being that magnesium oxide is omitted.

[0058] After obtaining the intermediate catalyst, the present invention mixes the intermediate catalyst and magnesium oxide and grinds them to obtain the bifunctional catalyst. In the present invention, the mass ratio of the intermediate catalyst to magnesium oxide is preferably 2 to 10:1, specifically 2:1, 4:1, 6:1, 8:1 or 10:1.

[0059] In the present invention, the grinding is preferably ball mill grinding or manual grinding, more preferably manual grinding; the grinding time is preferably 30 minutes.

[0060] In the present invention, after the grinding, the product is preferably tableted, crushed and sieved in sequence; the tableting pressure is preferably 5-15 MPa, specifically 10 MPa, and the holding time is preferably 10-30 min, specifically 20 min.

[0061] The present invention also provides the use of the bifunctional catalyst described in the above scheme or the bifunctional catalyst obtained by the preparation method described in the above scheme in catalyzing the hydrogenation of carbon dioxide to prepare methanol.

[0062] In the present invention, the application preferably includes the following steps: mixing the bifunctional catalyst with carbon dioxide and hydrogen to carry out a hydrogenation methanol reaction to obtain methanol.

[0063] In the present invention, the bifunctional catalyst is preferably reduced before use; the reduction equipment is preferably a fixed bed reactor; the gas used for the reduction is preferably hydrogen or a hydrogen-nitrogen mixture; the volume fraction of hydrogen in the hydrogen-nitrogen mixture is preferably 10%; the reduction temperature is preferably 200-350°C, specifically 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C or 350°C, the pressure is preferably normal pressure, and the insulation reduction time is preferably 8h.

[0064] In the present invention, the molar ratio of hydrogen to carbon dioxide is preferably 3:1.

[0065] In the present invention, the dosage of the bifunctional catalyst is preferably 0.8-1.5 mL, specifically 1 mL.

[0066] In the present invention, the volume space velocity of the hydrogenation reaction to produce methanol is preferably 2000 to 10000 mL mL cat -1 h -1 , specifically 2000mL mL cat -1 h -1 、4000mLmL cat -1 h -1 、6000mL mL cat -1 h -1 、8000mLmL cat -1 h -1 or 10000mL mL cat -1 h -1 .

[0067] In the present invention, the temperature of the hydrogenation to methanol reaction is preferably 200-350°C, specifically 200°C, 240°C, 270°C, 300°C, 320°C or 350°C; the pressure is preferably 2-15MPa, specifically 2MPa, 4MPa, 6MPa, 8MPa, 10MPa, 12MPa or 15MPa; the equipment for the hydrogenation to methanol reaction is preferably a fixed bed reactor.

[0068] In the bifunctional catalyst provided by the present invention, during the catalytic reaction process, copper exists in the form of single substance Cu and oxide, and other elements exist in the form of oxide.

[0069] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with embodiments, but they should not be understood as limiting the scope of protection of the present invention.

[0070] Example 1

[0071] (1) Preparation of catalyst:

[0072] 13.52 g Cu(NO 3 ) 2 ·3H 2 O, 8.32 g Zn(NO 3 ) 2 6H 2 O, 9.45gAl(NO 3 ) 3 6H 2 O, 1.07g Y(NO 3 ) 3 6H 2 O and 7.18 g Mg(NO 3 ) 2 6H 2 O is added into deionized water and stirred evenly to obtain 200 mL of mixed salt solution;

[0073] Add 14 g of sodium hydroxide and 7.42 g of sodium carbonate into 250 mL of deionized water and stir evenly to obtain a precipitant solution;

[0074] The mixed salt solution and the precipitant solution were simultaneously dropped into 200 mL of deionized water in a stirring state to form a blue precipitate. The dropping speed was adjusted to keep the pH value of the mixed solution at 10. When the mixed salt solution was added, the dropping of the precipitant solution was stopped.

[0075] The mixed salt solution and the precipitant solution are mixed and stirred at 60° C. for aging for 15 hours; after aging, the mixture is filtered to obtain a filter cake, and the filter cake is washed with deionized water until it is neutral; the washed filter cake is dried in an oven at 80° C. overnight for more than 12 hours, and after drying, it is ground to obtain a powdered precursor, which is then calcined at 500° C. for 4 hours in a muffle furnace, and a bifunctional catalyst is obtained after tableting, crushing and sieving; the composition of the bifunctional catalyst is Cu:Zn:Al:Y:Mg=50:25:22.5:2.5:25 (molar ratio)

[0076] (2) Carbon dioxide hydrogenation reaction activity test:

[0077] P=3.0MPa, T=250℃, GHSV=4000mLmL cat -1 h -1 , raw gas hydrogen / carbon dioxide (molar ratio) = 3, and the reaction activity is shown in Table 1.

[0078] Example 2

[0079] (1) Preparation of catalyst:

[0080] 11.11 g Cu(NO 3 ) 2 ·3H 2 O, 6.93g Zn(NO 3 ) 2 6H 2 O, 7.87gAl(NO 3 ) 3 6H 2 O, 0.89gY(NO 3 ) 3 6H 2 O and 11.96 g Mg(NO 3 ) 2 6H 2 O is added into deionized water and stirred evenly to obtain 200 mL of mixed salt solution;

[0081] Add 14 g of sodium hydroxide and 7.42 g of sodium carbonate into 250 mL of deionized water and stir evenly to obtain a precipitant solution;

[0082] The mixed salt solution and the precipitant solution were simultaneously dropped into 200 mL of deionized water in a stirring state to form a blue precipitate. The dropping speed was adjusted to keep the pH value of the mixed solution at 10. When the mixed salt solution was added, the dropping of the precipitant solution was stopped.

[0083] The mixed salt solution and the precipitant solution are mixed and stirred at 60°C for 15 hours; after aging, the filter cake is obtained by filtering, and the filter cake is washed with deionized water until it is neutral; the washed filter cake is dried in an oven at 80°C overnight for more than 12 hours, and after drying, it is ground to obtain a powdered precursor, which is then calcined at 500°C in a muffle furnace for 4 hours, and a bifunctional catalyst is obtained after tableting, crushing and sieving; the composition of the bifunctional catalyst is Cu:Zn:Al:Y:Mg=50:25:22.5:2.5:50 (molar ratio).

[0084] (2) Carbon dioxide hydrogenation reaction activity test:

[0085] P=3.0MPa, T=250℃, GHSV=4000mLmL cat -1 h -1 , raw gas hydrogen / carbon dioxide (substance ratio) = 3. The reaction activity is shown in Table 1.

[0086] Example 3

[0087] (1) Preparation of catalyst:

[0088] 16.74 g Cu(NO 3 ) 2 ·3H 2 O, 10.31 g Zn(NO 3 ) 2 6H 2 O, 11.69gAl(NO 3 ) 3 6H 2 O, 1.32gY(NO 3 ) 3 6H 2 O is added into deionized water and stirred evenly to obtain 200 mL of mixed salt solution;

[0089] Add 14 g of sodium hydroxide and 7.42 g of sodium carbonate into 250 mL of deionized water and stir evenly to obtain a precipitant solution;

[0090] The mixed salt solution and the precipitant solution were simultaneously dropped into 200 mL of deionized water in a stirring state to form a blue precipitate. The dropping speed was adjusted to keep the pH value of the mixed solution at 10. When the mixed salt solution was added, the dropping of the precipitant solution was stopped.

[0091] The mixed salt solution and the precipitant solution are mixed and stirred at 60°C for 15 hours; after aging, the filter cake is filtered to obtain a filter cake, and the filter cake is washed with deionized water until it is neutral; the washed filter cake is dried in an oven at 80°C overnight for more than 12 hours, and after drying, it is ground to obtain a powdered precursor, which is then calcined in a muffle furnace at 500°C for 4 hours to obtain a CuZnAlY catalyst.

[0092] 2 g of the CuZnAlY catalyst and 0.27 g of magnesium oxide powder were mixed and ground evenly, and then tableted, crushed and sieved to obtain a bifunctional catalyst; the chemical composition of the bifunctional catalyst was Cu: Zn: Al: Y: Mg = 50: 25: 22.5: 2.5: 25 (molar ratio)

[0093] (2) Carbon dioxide hydrogenation reaction activity test:

[0094] P=3.0MPa, T=250℃, GHSV=4000mLmL cat -1 h -1 , raw gas hydrogen / carbon dioxide (substance ratio) = 3. The reaction activity is shown in Table 1.

[0095] Example 4

[0096] (1) Preparation of catalyst:

[0097] 16.74 g Cu(NO 3 ) 2 ·3H 2 O, 10.31 g Zn(NO 3 ) 2 6H 2 O, 11.69gAl(NO 3 ) 3 6H 2 O, 1.32gY(NO 3 ) 3 6H 2 O is added into deionized water and stirred evenly to obtain 200 mL of mixed salt solution;

[0098] Add 14 g of sodium hydroxide and 7.42 g of sodium carbonate into 250 mL of deionized water and stir evenly to obtain a precipitant solution;

[0099] The mixed salt solution and the precipitant solution were simultaneously dropped into 200 mL of deionized water in a stirring state to form a blue precipitate. The dropping speed was adjusted to keep the pH value of the mixed solution at 10. When the mixed salt solution was added, the dropping of the precipitant solution was stopped.

[0100] The mixed salt solution and the precipitant solution are mixed and stirred at 60°C for 15 hours; after aging, the filter cake is filtered to obtain a filter cake, and the filter cake is washed with deionized water until it is neutral; the washed filter cake is dried in an oven at 80°C overnight for more than 12 hours, and after drying, it is ground to obtain a powdered precursor, which is then calcined in a muffle furnace at 500°C for 4 hours to obtain a CuZnAlY catalyst.

[0101] 2 g of the CuZnAlY catalyst and 0.54 g of magnesium oxide powder are mixed evenly and ground, and then tableted, crushed and sieved to obtain a bifunctional catalyst; the chemical composition of the bifunctional catalyst is Cu:Zn:Al:Y:Mg=50:25:22.5:2.5:50 (molar ratio).

[0102] (2) Carbon dioxide hydrogenation reaction activity test:

[0103] P=3.0MPa, T=250℃, GHSV=4000mLmL cat -1 h -1 , raw gas hydrogen / carbon dioxide (substance ratio) = 3. The reaction activity is shown in Table 1.

[0104] Example 5

[0105] (1) Preparation of catalyst:

[0106] 16.10 g Cu(NO 3 ) 2 ·3H2 O, 9.91g Zn(NO 3 ) 2 6H 2 O, 7.50gAl(NO 3 ) 3 6H 2 O, 2.55g Y(NO 3 ) 3 6H 2 O and 3.42 g Mg(NO 3 ) 2 6H 2 O is added into deionized water and stirred evenly to obtain 200 mL of mixed salt solution;

[0107] Add 14 g of sodium hydroxide and 7.42 g of sodium carbonate into 250 mL of deionized water and stir evenly to obtain a precipitant solution;

[0108] The mixed salt solution and the precipitant solution were simultaneously dropped into 200 mL of deionized water in a stirring state to form a blue precipitate. The dropping speed was adjusted to keep the pH value of the mixed solution at 10. When the mixed salt solution was added, the dropping of the precipitant solution was stopped.

[0109] The mixed salt solution and the precipitant solution are mixed and stirred at 60° C. for aging for 15 hours; after aging, the filter cake is filtered to obtain a filter cake, and the filter cake is washed with deionized water until it is neutral; the washed filter cake is dried in an oven at 80° C. overnight for more than 12 hours, and after drying, it is ground to obtain a powder precursor, and then calcined at 700° C. for 4 hours in a muffle furnace, and after tableting, crushing and sieving, a bifunctional catalyst is obtained; the chemical composition of the bifunctional catalyst is Cu: Zn: Al: Y: Mg = 50: 25: 15: 5: 10 (molar ratio)

[0110] (2) Carbon dioxide hydrogenation reaction activity test:

[0111] P=5.0MPa, T=220℃, GHSV=4000mLmL cat -1 h -1 , raw gas hydrogen / carbon dioxide (substance ratio) = 3. The reaction activity is shown in Table 1.

[0112] Example 6

[0113] (1) Preparation of catalyst:

[0114] 14.33 g Cu(NO 3 ) 2 ·3H 2 O, 8.82 g Zn(NO 3 ) 2 6H 2O, 8.90gAl(NO 3 ) 3 6H 2 O, 3.63g Y(NO 3 ) 3 6H 2 O and 4.56 g Mg(NO 3 ) 2 6H 2 O is added into deionized water and stirred evenly to obtain 200 mL of mixed salt solution;

[0115] Add 14 g of sodium hydroxide and 7.42 g of sodium carbonate into 250 mL of deionized water and stir evenly to obtain a precipitant solution;

[0116] The mixed salt solution and the precipitant solution were simultaneously dropped into 200 mL of deionized water in a stirring state to form a blue precipitate. The dropping speed was adjusted to keep the pH value of the mixed solution at 10. When the mixed salt solution was added, the dropping of the precipitant solution was stopped.

[0117] The mixed salt solution and the precipitant solution are mixed and stirred at 60° C. for aging for 15 hours; after aging, the filter cake is filtered to obtain a filter cake, and the filter cake is washed with deionized water until it is neutral; the washed filter cake is dried in an oven at 80° C. overnight for more than 12 hours, and after drying, it is ground to obtain a powder precursor, and then calcined at 700° C. for 4 hours in a muffle furnace, and after tableting, crushing and sieving, a bifunctional catalyst is obtained; the chemical composition of the bifunctional catalyst is Cu: Zn: Al: Y: Mg = 50: 25: 20: 8: 15 (molar ratio)

[0118] (2) Carbon dioxide hydrogenation reaction activity test:

[0119] P=5.0MPa, T=270℃, GHSV=6000mLmL cat -1 h -1 , raw gas hydrogen / carbon dioxide (substance ratio) = 3. The reaction activity is shown in Table 1.

[0120] Example 7

[0121] (1) Preparation of catalyst:

[0122] 8.33 g Cu(NO 3 ) 2 ·3H 2 O, 5.13gZn(NO 3 ) 2 6H 2 O, 4.66gAl(NO 3 ) 3 6H 2 O, 2.64gY(NO3 ) 3 6H 2 O and 17.68 g Mg(NO 3 ) 2 6H 2 O was added into deionized water and stirred to obtain 200 mL of mixed salt solution;

[0123] Add 14 g of sodium hydroxide and 7.42 g of sodium carbonate into 250 mL of deionized water and stir evenly to obtain a precipitant solution;

[0124] The mixed salt solution and the precipitant solution were simultaneously dropped into 200 mL of deionized water in a stirring state to form a blue precipitate. The dropping speed was adjusted to keep the pH value of the mixed solution at 10. When the mixed salt solution was added, the dropping of the precipitant solution was stopped.

[0125] The mixed salt solution and the precipitant solution are mixed and stirred at 60°C for 15 hours; after aging, the filter cake is filtered to obtain a filter cake, and the filter cake is washed with deionized water until it is neutral; the washed filter cake is dried in an oven at 80°C overnight for more than 12 hours, and after drying, it is ground to obtain a powdered precursor, which is then calcined in a muffle furnace at 300°C for 4 hours to obtain a CuZnAlY catalyst.

[0126] 2 g of the CuZnAlY catalyst and 0.79 g of magnesium oxide powder are mixed evenly and ground, and then tableted, crushed and sieved to obtain a bifunctional catalyst; the chemical composition of the bifunctional catalyst is Cu:Zn:Al:Y:Mg=50:25:18:10:100 (molar ratio).

[0127] (2) Carbon dioxide hydrogenation reaction activity test:

[0128] P=10.0MPa, T=300℃, GHSV=8000mLmL cat -1 h -1 , raw gas hydrogen / carbon dioxide (substance ratio) = 3. The reaction activity is shown in Table 1.

[0129] Example 8

[0130] (1) Preparation of catalyst:

[0131] 16.50 g Cu(NO 3 ) 2 ·3H 2 O, 10.16 g Zn(NO 3 ) 2 6H 2 O, 11.52gAl(NO 3 ) 3 6H 2O, 1.31gY(NO 3 ) 3 6H 2 O and 0.88 g Mg(NO 3 ) 2 6H 2 O is added into deionized water and stirred evenly to obtain 200 mL of mixed salt solution;

[0132] Add 14 g of sodium hydroxide and 7.42 g of sodium carbonate into 250 mL of deionized water and stir evenly to obtain a precipitant solution;

[0133] The mixed salt solution and the precipitant solution were simultaneously dropped into 200 mL of deionized water in a stirring state to form a blue precipitate. The dropping speed was adjusted to keep the pH value of the mixed solution at 10. When the mixed salt solution was added, the dropping of the precipitant solution was stopped.

[0134] After the mixed salt solution and the precipitant solution are mixed, they are stirred and aged at 60°C for 15 hours; after aging, the filter cake is filtered to obtain a filter cake, and the filter cake is washed with deionized water until it is neutral; the washed filter cake is dried in an oven at 80°C overnight for more than 12 hours, and after drying, it is ground to obtain a powdered precursor, which is then calcined at 500°C in a muffle furnace for 4 hours, and a bifunctional catalyst is obtained after tableting, crushing and sieving; the chemical composition of the bifunctional catalyst is Cu:Zn:Al:Y:Mg=50:25:22.5:2.5:2.5 (molar ratio).

[0135] (2) Carbon dioxide hydrogenation reaction activity test:

[0136] P=3.0MPa, T=250℃, GHSV=4000mLmL cat -1 h -1 , raw gas hydrogen / carbon dioxide (substance ratio) = 3. The reaction activity is shown in Table 1.

[0137] Example 9

[0138] (1) Preparation of catalyst:

[0139] 16.50 g Cu(NO 3 ) 2 ·3H 2 O, 10.16 g Zn(NO 3 ) 2 6H 2 O, 11.52gAl(NO 3 ) 3 6H 2 O, 1.31gY(NO 3 ) 3 6H 2O and 0.88 g Mg(NO 3 ) 2 6H 2 O is added into deionized water and stirred evenly to obtain 200 mL of mixed salt solution;

[0140] Add 14 g of sodium hydroxide and 7.42 g of sodium carbonate into 250 mL of deionized water and stir evenly to obtain a precipitant solution;

[0141] The mixed salt solution and the precipitant solution were simultaneously dropped into 200 mL of deionized water in a stirring state to form a blue precipitate. The dropping speed was adjusted to keep the pH value of the mixed solution at 10. When the mixed salt solution was added, the dropping of the precipitant solution was stopped.

[0142] After the mixed salt solution and the precipitant solution are mixed, they are stirred and aged at 60°C for 15 hours; after aging, the filter cake is filtered to obtain a filter cake, and the filter cake is washed with deionized water until it is neutral; the washed filter cake is dried in an oven at 80°C overnight for more than 12 hours, and after drying, it is ground to obtain a powdered precursor, which is then calcined at 500°C in a muffle furnace for 4 hours, and a bifunctional catalyst is obtained after tableting, crushing and sieving; the chemical composition of the bifunctional catalyst is Cu:Zn:Al:Y:Mg=50:25:22.5:2.5:2.5 (molar ratio).

[0143] (2) Carbon dioxide hydrogenation reaction activity test:

[0144] P=5.0MPa, T=250℃, GHSV=4000mLmL cat -1 h -1 , raw gas hydrogen / carbon dioxide (substance ratio) = 3. The reaction activity is shown in Table 1.

[0145] Example 10

[0146] (1) Preparation of catalyst:

[0147] 16.50 g Cu(NO 3 ) 2 ·3H 2 O, 10.16 g Zn(NO 3 ) 2 6H 2 O, 11.52gAl(NO 3 ) 3 6H 2 O, 1.31gY(NO 3 ) 3 6H 2 O and 0.88 g Mg(NO 3 ) 2 6H 2O is added into deionized water and stirred evenly to obtain 200 mL of mixed salt solution;

[0148] Add 14 g of sodium hydroxide and 7.42 g of sodium carbonate into 250 mL of deionized water and stir evenly to obtain a precipitant solution;

[0149] The mixed salt solution and the precipitant solution were simultaneously dropped into 200 mL of deionized water in a stirring state to form a blue precipitate. The dropping speed was adjusted to keep the pH value of the mixed solution at 10. When the mixed salt solution was added, the dropping of the precipitant solution was stopped.

[0150] After the mixed salt solution and the precipitant solution are mixed, they are stirred and aged at 60°C for 15 hours; after aging, the filter cake is filtered to obtain a filter cake, and the filter cake is washed with deionized water until it is neutral; the washed filter cake is dried in an oven at 80°C overnight for more than 12 hours, and after drying, it is ground to obtain a powdered precursor, which is then calcined at 500°C in a muffle furnace for 4 hours, and a bifunctional catalyst is obtained after tableting, crushing and sieving; the chemical composition of the bifunctional catalyst is Cu:Zn:Al:Y:Mg=50:25:22.5:2.5:2.5 (molar ratio).

[0151] (2) Carbon dioxide hydrogenation reaction activity test:

[0152] P=3.0MPa, T=220℃, GHSV=4000mLmL cat -1 h -1 , raw gas hydrogen / carbon dioxide (substance ratio) = 3. The reaction activity is shown in Table 1.

[0153] Embodiment 11

[0154] (1) Preparation of catalyst:

[0155] 16.50 g Cu(NO 3 ) 2 ·3H 2 O, 10.16 g Zn(NO 3 ) 2 6H 2 O, 11.52gAl(NO 3 ) 3 6H 2 O, 1.31gY(NO 3 ) 3 6H 2 O and 0.88 g Mg(NO 3 ) 2 6H 2 O is added into deionized water and stirred evenly to obtain 200 mL of mixed salt solution;

[0156] Add 14 g of sodium hydroxide and 7.42 g of sodium carbonate into 250 mL of deionized water and stir evenly to obtain a precipitant solution;

[0157] The mixed salt solution and the precipitant solution were simultaneously dropped into 200 mL of deionized water in a stirring state to form a blue precipitate. The dropping speed was adjusted to keep the pH value of the mixed solution at 10. When the mixed salt solution was added, the dropping of the precipitant solution was stopped.

[0158] After the mixed salt solution and the precipitant solution are mixed, they are stirred and aged at 60°C for 15 hours; after aging, the filter cake is filtered to obtain a filter cake, and the filter cake is washed with deionized water until it is neutral; the washed filter cake is dried in an oven at 80°C overnight for more than 12 hours, and after drying, it is ground to obtain a powdered precursor, which is then calcined at 500°C in a muffle furnace for 4 hours, and a bifunctional catalyst is obtained after tableting, crushing and sieving; the chemical composition of the bifunctional catalyst is Cu:Zn:Al:Y:Mg=50:25:22.5:2.5:2.5 (molar ratio).

[0159] (2) Carbon dioxide hydrogenation reaction activity test:

[0160] P=3.0MPa, T=250℃, GHSV=8000mLmL cat -1 h -1 , raw gas hydrogen / carbon dioxide (substance ratio) = 3. The reaction activity is shown in Table 1.

[0161] Comparative Example 1

[0162] (1) Preparation of catalyst:

[0163] 16.91 g Cu(NO 3 ) 2 ·3H 2 O, 10.41 g Zn(NO 3 ) 2 6H 2 O, 11.81gAl(NO 3 ) 3 6H 2 O and 1.34gY(NO 3 ) 3 6H 2 O is added into deionized water and stirred evenly to obtain 200 mL of mixed salt solution;

[0164] Add 14 g of sodium hydroxide and 7.42 g of sodium carbonate into 250 mL of deionized water and stir evenly to obtain a precipitant solution;

[0165] The mixed salt solution and the precipitant solution were simultaneously dropped into 200 mL of deionized water in a stirring state to form a blue precipitate. The dropping speed was adjusted to keep the pH value of the mixed solution at 10. When the mixed salt solution was added, the dropping of the precipitant solution was stopped.

[0166] The mixed salt solution and the precipitant solution are mixed and stirred at 60° C. for 15 hours; after aging, the filter cake is filtered to obtain a filter cake, and the filter cake is washed with deionized water until it is neutral; the washed filter cake is dried in an oven at 80° C. overnight for more than 12 hours, and after drying, it is ground to obtain a powder precursor, which is then calcined at 500° C. for 4 hours in a muffle furnace, and a bifunctional catalyst is obtained after tableting, crushing and sieving; the chemical composition of the bifunctional catalyst is Cu: Zn: Al: Y = 50: 25: 22.5: 2.5 (molar ratio)

[0167] (2) Carbon dioxide hydrogenation reaction activity test:

[0168] P=3.0MPa, T=250℃, GHSV=4000mLmL cat -1 h -1 , raw gas hydrogen / carbon dioxide (substance ratio) = 3. The reaction activity is shown in Table 1.

[0169] Test Example 1

[0170] After reducing the bifunctional catalysts of Examples 1 to 11 and Comparative Example 1, carbon dioxide gas was introduced and the carbon dioxide adsorption amount (carbon dioxide adsorption amount of the catalyst after reduction) was measured as shown in Table 1.

[0171] Table 1 Catalytic activity of the bifunctional catalyst of Examples 1 to 11 and Comparative Example 1

[0172]

[0173]

[0174] According to Table 1, compared with the CuZnAlY catalyst of Comparative Example 1, the bifunctional catalyst of the embodiment with MgO added has a higher carbon dioxide adsorption capacity, indicating that the addition of Mg improves the adsorption capacity of the catalyst for carbon dioxide; compared with Comparative Example 1, in Example 8, under the same reaction conditions and the same ratio of Cu, Zn, Al and Y, the introduction of Mg element improves the methanol selectivity; compared with Comparative Example 1, in Example 9, under the same ratio of Cu, Zn, Al and Y, the reaction pressure is increased to improve the methanol selectivity; compared with Comparative Example 1, in Example 10, under the same ratio of Cu, Zn, Al and Y, the reaction temperature is reduced to improve the methanol selectivity; compared with Comparative Example 1, in Example 11, under the same ratio of Cu, Zn, Al and Y, the space velocity is increased to improve the methanol space-time yield; the bifunctional catalyst Cu in Example 6 50 Zn 25 Al 20 Y 8 Mg 15 At normal pressure and 50°C, the adsorption capacity of carbon dioxide reaches 4684 μmol / g, and at 270°C, 5MPa, GHSV=6000mLmL cat -1 h -1 Under these conditions, the conversion rate of carbon dioxide and the selectivity of methanol reached 26.56% and 76.46%, respectively.

[0175] Test Example 2

[0176] The catalyst of Example 9 was heated at P = 5.0 MPa, T = 250 °C, GHSV = 4000 mL / min. cat -1 h -1 , the stability test was carried out under the reaction conditions of raw gas hydrogen / carbon dioxide (molar ratio) = 3, and the results are shown in Table 2.

[0177] Table 2 Test Example 2 Stability Test Results

[0178]

[0179]

[0180] It can be seen from Table 2 that the bifunctional catalyst provided by the present invention has good activity, high stability, and a long service life of more than 720 hours.

[0181] It can be seen from the above embodiments that the bifunctional catalyst provided by the present invention has high carbon dioxide conversion rate and methanol selectivity, with the carbon dioxide conversion rate reaching 26.56% and the methanol selectivity reaching 76.46%. It has high stability and long service life, and is suitable for catalyzing carbon dioxide hydrogenation to produce methanol.

[0182] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A bifunctional catalyst, characterized in that: including metal oxides, including copper oxide, zinc oxide, aluminum oxide, yttrium oxide and magnesium oxide; The molar ratio of copper in the copper oxide to zinc in the zinc oxide is 50:25; The molar ratio of copper in the copper oxide to aluminum in the aluminum oxide is 50:15-25; The molar ratio of copper in the copper oxide to yttrium in the yttrium oxide is 50:1-10; The molar ratio of copper in the copper oxide to magnesium in the magnesium oxide is 50:27-150.

2. The bifunctional catalyst according to claim 1, characterized in that The copper oxide is CuO.

3. The bifunctional catalyst according to claim 1 or 2, characterized in that The zinc oxide is ZnO.

4. The bifunctional catalyst according to claim 1, characterized in that The aluminum oxide is Al2O3.

5. The bifunctional catalyst according to claim 1 or 4, characterized in that: The yttrium oxide is Y2O3.

6. The bifunctional catalyst according to claim 1, characterized in that The magnesium oxide is MgO.

7. The bifunctional catalyst according to claim 1 or 2, characterized in that: The particle size of the bifunctional catalyst is 250-425 μm.

8. The method for preparing the bifunctional catalyst according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: Copper salt, zinc salt, aluminum salt, yttrium salt, magnesium salt and water are mixed to obtain a mixed salt solution, sodium hydroxide and sodium carbonate are mixed to obtain a precipitant solution, the mixed salt solution and the precipitant solution are dripped into water to obtain a mixed solution, the pH value of the mixed solution is maintained at 9.5-10.5 during the dripping process, the mixed solution is aged and then roasted to obtain the bifunctional catalyst.

9. The method for preparing the bifunctional catalyst according to any one of claims 1 to 7, characterized in that: The invention comprises a mechanical mixing method; the mechanical mixing method comprises the following steps: mixing copper salt, zinc salt, aluminum salt, yttrium salt and water to obtain a mixed salt solution; mixing sodium hydroxide and sodium carbonate to obtain a precipitant solution; dripping the mixed salt solution and the precipitant solution into water to obtain a mixed solution, maintaining the pH value of the mixed solution at 9.5-10.5 during the dripping process, aging the mixed solution and then calcining it to obtain an intermediate catalyst; mixing the intermediate catalyst and magnesium oxide and grinding them to obtain the bifunctional catalyst.

10. Use of the bifunctional catalyst according to any one of claims 1 to 7 or the bifunctional catalyst obtained by the preparation method according to any one of claims 8 to 9 in catalyzing the hydrogenation of carbon dioxide to produce methanol.

Citation Information

Patent Citations

  • Catalyst for preparing methyl alcohol by carbon dioxide catalytic hydrogenation and preparing method thereof

    CN102000578A

  • Catalyst for synthesizing methanol through carbon dioxide hydrogenation as well as preparation method and application thereof

    CN103263926A

  • Methanol catalyst synthesized by carbon dioxide hydrogenation, preparation method and application thereof

    CN105013492A

  • Catalyst for preparing methanol through carbon dioxide hydrogenation and preparation method thereof

    CN116764641A

  • Catalyst for synthesis of methanol

    JP1998277392A